Post-Pandemic Tourism: An Article on the Recovery Strategies - Sunder, Sidharth; Dixit, Swarnika (Integrated Journal for Research in Arts and Humanities, 2023)
The spread of the COVID 19 Pandemic has been a black-swan event (Yan, 2020), in the history of humanity. Having affected over 180 countries globally, the Corona Virus put a halt to the daily activities of mankind. Business, Trade, and the Overall Economy of the world went downhill due to this event. Today, we see people commuting to different countries and pursuing their endeavours after having been prevented from moving out of their homes for a good part of over a year. Manufacturing, Transportation, Warehousing, Tourism, Education, and Accommodation were among the highly impacted industries. In such turbulent times, the Information Technology (Rahul De', 2020) sector played a pivotal role in improving the overall operational standards of businesses across the world. The Tourism Industry especially, has had a massive setback primarily due to the restrictions on traveling imposed by governments across the world. This research paper will probe into the emerging trends and propositions by different organizations into improving tourism and making it sustainable for the future. It will further shed light on redefining destination marketing and promotion of domestic tourism as a recovery strategy to rejuvenate the industry and restore its pre-eminence in the economy.